The exploitation and opportunities of tourism potential of regions lagging behind in South-Transdanubia - Berki Mónika; Csapó János (Journal for Geography, 2006)
If we have a look at the „negative regions” or in other words the regions lagging behind in Hungary, we can distinguish between external and internal peripheries. The external peripheries are associated with border areas, the internal ones with agricultural activities. In these micro regions unemployment rate is above the national average, income position is below the average, the share of foreign capital and entrepreneurial activity is low. Those micro regions facing the problems of bordering areas can be found at almost every bordering areas except for the western region, while the ones facing the sectoral problems of agriculture dominated areas (internal peripheries) can be highlighted in South-Transdanubia (Baranya, Somogy and Tolna counties), or North East Hungary (Hajdúság). Most of these regions though are rich in natural and cultural resources (national parks, protected natural areas of course due to their bordering function they have not been disturbed by economic activities) which may offer opportunities for tourism. The appearing problems of development include the poor infrastructure of the towns and villages, the higher than average ratio of poverty ridden residential areas and the low standard of community services and public utilities. In our study we chose two micro regions with characteristic features to demonstrate the problem on a micro regional level.